2009
DOI: 10.17159/2413-3051/2010/v20i2a3300
|View full text |Cite
|
Sign up to set email alerts
|

Stakeholder perceptions in the factors constraining the development and implementation of public private partnerships in the Ugandan electricity sector

Abstract: Amidst increasingly constrained public budgets and inadequate service delivery, private sector participation through public private partnerships is increasingly being used as a means for delivering physical infrastructure. The government of Uganda, which is currently grappling with a crippling electricity power deficit, has over the years, pursued a number of strategies to encourage private sector participation in the electricity sector, but with limited success. This paper presents the findings of research in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 11 publications
(9 reference statements)
0
13
0
Order By: Relevance
“…Issues, such as corruption (documented by Lilley [74][75][76]), long administrative processes (documented by Ranjit and Kazim [77]), and political interference (as highlighted by Sader [78]) are also frequently mentioned in innovation studies in sub-Saharan Africa. This poor institutional setting and the inability of local institutions to provide a healthy environment to enable tools, such as PPPs, in RI to be implemented are commonly identified as factors that constrain private participation in the sub-Saharan Africa context [79,80]. Our research found that even when there are policies and programs promoting the interconnectivity of STI across national sectors, the level of coherence between them is relatively weak.…”
Section: Identification Of Systemic Bottlenecks Between Sgcs and Othementioning
confidence: 74%
“…Issues, such as corruption (documented by Lilley [74][75][76]), long administrative processes (documented by Ranjit and Kazim [77]), and political interference (as highlighted by Sader [78]) are also frequently mentioned in innovation studies in sub-Saharan Africa. This poor institutional setting and the inability of local institutions to provide a healthy environment to enable tools, such as PPPs, in RI to be implemented are commonly identified as factors that constrain private participation in the sub-Saharan Africa context [79,80]. Our research found that even when there are policies and programs promoting the interconnectivity of STI across national sectors, the level of coherence between them is relatively weak.…”
Section: Identification Of Systemic Bottlenecks Between Sgcs and Othementioning
confidence: 74%
“…In recent years, the public-private partnership (PPP) is widely used in power supply [1], water supply [2], sewage and garbage disposal [3,4], traffic [5,6], pipes [7], and other public infrastructure construction fields and has become the main way of governments to provide public service [8,9]. Public-private partnership refers to a cooperative relationship formed between government and private organizations, in order to build infrastructure projects or provide some public goods and services [10].…”
Section: Introductionmentioning
confidence: 99%
“…Fourth, results of multilayer perceptron model showed that the top three most influenced factors on total construction time delay are number of investors, experiences of management unit and number of provinces. With two out of top three factors are related to number of stakeholders, it is suggested that there is probably an issue of interest conflict among stakeholders [31] or a lack of a good coordination between stakeholders [18,32]. As such, future projects should focus on the problem of interest conflict as well as the coordination between stakeholders.…”
Section: Discussionmentioning
confidence: 99%
“…Another research effort of Babatunde and others [15] has pointed out ten group factors considered as barriers to PPP projects in Nigeria context. Among those, a problem caused by delays has been revealed including receiving payments [16], negotiations, lengthy bureaucratic procedures or political debates [17,18].…”
Section: Introductionmentioning
confidence: 99%